The Terror Attacks of 9/11 and Suicides in Germany: A Time Series Analysis. Issue 15 (April 2016) - Medenwald, Daniel
Abstract : Abstract: Data on the effect of the September 11, 2001 (9/11) terror attacks on suicide rates remain inconclusive. Reportedly, even people located far from the attack site have considerable potential for personalizing the events that occurred on 9/11. Durkheim's theory states that suicides decrease during wartime; thus, a decline in suicides might have been expected after 9/11. We conducted a time series analysis of 164, 136 officially recorded suicides in Germany between 1995 and 2009 using the algorithm introduced by Box and Jenkins. Compared with the average death rate, we observed no relevant change in the suicide rate of either sex after 9/11. Our estimates of an excess of suicides approached the null effect value on and within a 7-day period after 9/11, which also held when subsamples of deaths in urban or rural settings were examined. No evidence of Durkheim's theory attributable to the 9/11attacks was found in this sample.